Comparative Analysis of High-Velocity Versus Low-Velocity Exercise on Outcomes After Total Knee Arthroplasty: A Randomized Clinical Trial. Issue 4 (October 2016) - Kelly, Marie A.; Finley, Margaret; Lichtman, Steven W.; Hyland, Matthew R.; Edeer, Ayse Ozcan
Abstract : Background and Purpose: High-velocity (HV) exercise is defined as performing a concentric muscle contraction as fast as possible, or in 1 second or less. Low-velocity (LV) exercise is defined as using 2 seconds to complete the contraction. A comparison of HV to LV exercise performed by community dwelling older adults indicates that HV exercise produces greater gains in power and scores for the 8-ft up-and-go, 30-seond chair stand, and continuous scale physical function performance tests. The effectiveness of HV strengthening exercises has not been identified for individuals who undergo total knee arthroplasty (TKA). The purpose of this research study was to compare the effects of a 6-week exercise program, using either LV or HV contractions, on functional performance, gait, and pain of individuals who have undergone TKA. Methods: Adults aged 60 to 89 years with a mean (standard deviation) age of 71.2 (6.8) years who underwent TKA an average of 15 days prior were randomly assigned to an HV exercise (n = 19) or LV exercise (n = 19) training group. The training program lasted for 12 sessions, over 6 to 7 weeks. The primary outcome was functional performance rated with the 6-Minute Walk Test. Secondary measures were the stair climb test, Timed Up and Go test, gait velocity, gait deviations measured with the Gait Abnormality Rating Scale, and pain via a visual analog scale. A 2×2 mixed model analysis of variance (group × time) was used for all outcomes. Comparison between LV and HV groups for posttest gait velocity and Gait Abnormality Rating Scale used independent t test and Mann-Whitney U test, respectively. Results: At baseline no differences between groups were noted for sex, age, and height. The LV group weighed more and had more comorbid conditions. Spearman's ρ demonstrated that the greater comorbidities of the LV group correlated with a slower stair climb test at baseline. At posttest both groups exhibited significantly improved scores for all outcome measurements except the visual analog scale for pain. The HV group, but not the LV group, reported a significant decrease in pain at the end of the 6-week training program. Conclusions: Both HV and LV progressive exercises equally improve functional performance. Only the HV group reported significantly decreased pain at posttest.